Kemampuan Membaca Pemahaman Mahasiswa Calon Guru Sekolah Dasar - Ahmad Rif'an Najih; Azhar Syarifuddin (STKIP AL HIKMAH SURABAYA, 2024)
Reading comprehension ability is the key to success in education. Good reading comprehension ability can help students deeply understand the contents of a reading so that students' knowledge can develop. Elementary school teachers have an important role in teaching students and instilling the foundation of this reading skill at an early level. However, before being able to pursue reading skills, as individuals, teachers must also have good reading skills. This study aims to describe the reading comprehension ability of prospective elementary school teachers. The study was conducted by providing a reading comprehension ability test consisting of 40 objective questions. The questions compiled revealed 3 levels of reading ability, namely factual, interpretive and applicable. The test result data were analyzed quantitatively using descriptive statistics. The results of the study showed that the reading comprehension ability of prospective elementary school teachers was included in the good category with a score of 77.5 (out of 100). Furthermore, factual and interpretive reading abilities were included in the good category with scores of 75 and 73.5 respectively. While the aspect of students' applicable reading ability was included in the very good category with a score of 88.